2015
DOI: 10.1128/aem.01562-15
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Microbiota of Ixodes Ticks with Regard to Geography, Species, and Sex

Abstract: n Ixodes scapularis is the principal vector of Lyme disease on the East Coast and in the upper Midwest regions of the UnitedStates, yet the tick is also present in the Southeast, where Lyme disease is absent or rare. A closely related species, I. affinis, also carries the pathogen in the South but does not seem to transmit it to humans. In order to better understand the geographic diversity of the tick, we analyzed the microbiota of 104 adult I. scapularis and 13 adult I. affinis ticks captured in 19 locations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

41
214
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(263 citation statements)
references
References 43 publications
(48 reference statements)
41
214
8
Order By: Relevance
“…In addition, they carry numerous endosymbionts and commensals, which may provide nutrient supplements to the tick and also affect vector competence (reviewed in (Narasimhan & Fikrig, ; Bonnet et al., ; Clay & Fuqua, )). Studies have reported that the tick microbial community is variable depending on several factors such as source of host blood meal (Rynkiewicz, Hemmerich, Rusch, Fuqua, & Clay, ), feeding status (Menchaca et al., ; Swei & Kwan, ; Zhang et al., ), tick species, life stage, gender, and geographical origin (Carpi et al., ; Van Treuren et al., ; Williams‐Newkirk, Rowe, Mixson‐Hayden, & Dasch, ). However, very few studies have focused on the tick microbiome differences based on environmental conditions such as seasons of collection (Lalzar, Harrus, Mumcuoglu, & Gottlieb, ) or the immediate environment (Menchaca et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they carry numerous endosymbionts and commensals, which may provide nutrient supplements to the tick and also affect vector competence (reviewed in (Narasimhan & Fikrig, ; Bonnet et al., ; Clay & Fuqua, )). Studies have reported that the tick microbial community is variable depending on several factors such as source of host blood meal (Rynkiewicz, Hemmerich, Rusch, Fuqua, & Clay, ), feeding status (Menchaca et al., ; Swei & Kwan, ; Zhang et al., ), tick species, life stage, gender, and geographical origin (Carpi et al., ; Van Treuren et al., ; Williams‐Newkirk, Rowe, Mixson‐Hayden, & Dasch, ). However, very few studies have focused on the tick microbiome differences based on environmental conditions such as seasons of collection (Lalzar, Harrus, Mumcuoglu, & Gottlieb, ) or the immediate environment (Menchaca et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…; Van Treuren et al . ). Although the role of the blacklegged tick as a vector of the Lyme disease spirochete ( Borrelia burgdorferi ) and the babesiosis protozoan ( Babesia microti ) has been known since the late 1970s (Spielman ; Steere et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Van Treuren et al . ), while only a few have examined specific tissues and organs (Andreotti et al . ; Budachetri et al .…”
Section: Introductionmentioning
confidence: 99%
“…The microbiota modifies the ability of a host to be affected by, and to transmit, pathogens. Thus, understanding the relationship between microbiota and arthropod disease vectors, including mosquitoes, may impact mitigation of emerging infectious diseases (Dennison et al, 2014; Van Treuren et al, 2015). …”
Section: Introductionmentioning
confidence: 99%